Real‐life data on treatment and outcomes in advanced ovarian cancer: An observational, multinational cohort study (RESPONSE trial). Issue 16 (17th June 2022) - Marth, Christian; Abreu, Miguel Henriques; Andersen, Klaus Kaae; Aro, Karoliina M.; de Lurdes Batarda, Maria; Boll, Dorry; Ekmann‐Gade, Anne Weng; Haltia, Ulla‐Maija; Hansen, Jesper; Haug, Ala Jabri; Høgdall, Claus; Korach, Jacob; et al.
Abstract : Background: This study aimed to describe the treatment strategies and outcomes for women with newly diagnosed advanced high‐grade serous or endometrioid ovarian cancer (OC). Methods: This observational study collected real‐world medical record data from eight Western countries on the diagnostic workup, clinical outcomes, and treatment of adult women with newly diagnosed advanced (Stage III–IV) high‐grade serous or endometrioid OC. Patients were selected backward in time from April 1, 2018 (the index date), with a target of 120 patients set per country, followed for ≥20 months. Results: Of the 1119 women included, 66.9% had Stage III disease, 11.7% had a deleterious BRCA mutation, and 26.6% received bevacizumab; 40.8% and 39.3% underwent primary debulking surgery (PDS) and interval debulking surgery (IDS), respectively. Of the patients who underwent PDS, 55.5% had no visible residual disease (VRD); 63.9% of the IDS patients had no VRD. According to physician‐assessed responses (at the first assessment after diagnosis and treatment), 53.2% of the total population had a complete response and 25.7% had a partial response to first‐line chemotherapy after surgery. After ≥20 months of follow‐up, 32.9% of the patients were disease‐free, 46.4% had progressive disease, and 20.6% had died. Bevacizumab use had a significant positive effect on overall survival (hazard ratio [HR], 0.62; 95% CI, 0.42–0.91; p = .01). A deleterious BRCA status had a significant positive effect on progression‐free survival (HR, 0.60; 95% CI, 0.41–0.84; p < . 01). Conclusions: Women with advanced high‐grade serous or endometrioid OC have a poor prognosis. Bevacizumab use and a deleterious BRCA status were found to improve survival in this real‐world population. Lay summary: Patients with advanced (Stage III or IV) ovarian cancer (OC) have a poor prognosis. The standard treatment options of surgery and chemotherapy extend life beyond diagnosis for 5 years or more in only approximately 45% of patients. This study was aimed at describing the standard of care in eight Western countries and estimating how many patients who are diagnosed with high‐grade serous or endometrioid OC could potentially be eligible for first‐line poly(adenosine diphosphate ribose) polymerase inhibitor (PARPi) maintenance therapy. The results highlight the poor prognosis for these patients and suggest that a significant proportion (79%) would potentially be eligible for first‐line PARPi maintenance treatment. Abstract : In women diagnosed with high‐grade advanced serous or endometrioid ovarian cancer, bevacizumab use had a significant positive effect on overall survival (hazard ratio [HR], 0.62; 95% CI, 0.42–0.91; p = .01), and a deleterious BRCA status had a significant positive effect on progression‐free survival (HR, 0.60; 95% CI, 0.41–0.84; p < . 01). According to clinical responses following surgery and first‐line chemotherapy, almost 8 in 10 women diagnosed with high‐grade advanced serous or endometrioid ovarian cancer would potentially be eligible for first‐line poly(adenosine diphosphate ribose) polymerase inhibitor maintenance treatment.